PHOTOSYNTHETIC RESPONSES OF Eucalyptus nitens Maiden AT INITIAL STAGES OF ROOT-ROT INFECTION - Agustini, Luciasih; Beadle, Chris; Barry, Karen; Mohammed, Caroline (Secretariat of Forestry Research and Development Agency, 2015)
Photosynthetic responses associated with initial stages of root-rot disease have been studied through setting up an artificial inoculation of Eucalyptus nitens trees with a root-rot pathogen, Armillaria luteobubalina. Trees were inoculated with two different strains of A. luteobubalina. Root systems were either wounded or left intact before inoculation. Three photosynthetic parameters, i.e. photosystem II yield (Fv/Fm), chlorophyll content and photosynthetic rate (Amax) were assessed during six-months of observation. Photosystem II yield was the most sensitive to root-rot infection. A significant difference in Fv/Fm between the unwounded control (UW-P0) and other treatments was observed, and the difference was affected by interaction between time and treatment factors (F- ratio = 3.798, p-value = 0.005). Chlorophyll content and photosynthetic rate (Amax) decreased for all trees, including controls, during the period of the experiment. The decrease was more marked in treated than control trees, and the changes more determined by the time factor (p-value <0.0001). The root systems of inoculated trees were examined and re-isolations of A. luteobubalina from symptomatic roots were carried out to confirm infection with A.luteobubalina of E. nitens trees. This preliminary trial was successful and did indicate that there were detectable physiological changes associated with early infection of root-rot. However the experiment required a longer duration for more widespread physiological changes to be detected.